Trombose de veia porta após cateterismo venoso umbilical: revisão da epidemiologia, profilaxia, diagnóstico e tratamento - José Ricardo Borém Lopes (2017)
The extrahepatic obstruction of the portal vein is one of the most important causes of upper gastrointestinal bleeding in children. Studies about its physiopathology reveals that umbilical vein catheterization during the neonatal period is one of the most relevant risk factor. There are few data on the incidence, prevalence, risk factors and the effect of treatment of portal vein thrombosis in the newborn. It was conducted a search in the database of the MEDLINE, PUBMED, Elsevier, Web of Science, Scielo e Lilacs and included articles in Portuguese and English. The incidence of portal vein thrombosis after umbilical vein catheterization varies from 1% to 43% depending on the population, the moment of the ultrasound and the design of the study. The main risk factors are sepsis and longtime of catheterization. It is still not clear if the treatment with anticoagulation, either heparin or tissue plasminogen activator, changes the prognosis. If chooses to treat, it should be done with heparin; the thrombolysis reserved for the cases where there is limb, organ, or life threatening thromboses. Spontaneous regression of neonatal portal vein thrombosis is common but about 3% of these patients progress to extrahepatic obstruction of the portal vein and portal hypertension.